ANALISIS KEBIJAKAN DAERAH DALAM RANGKA PENGELOLAAN HUTAN LINDUNG WEHEA DI KABUPATEN KUTAI TIMUR - Aliri, Aliri (Jurnal Warta Rimba, 2014)
This research was conducted in Wehea Protected forest in the district of East Kutai Regency Kongbeng . The purpose of this study is to identify and assess the policies ( rules and activity programs ) East Kutai regional government in managing Wehea forest .The research was using GAP Method to analyze the policies implementation that applicable in central government and East Kutai in relationship with the fact of Wehea Protected Forest management from some aspects such as human resources, forest resources, institutional and social. Analysis revealedÂ  that the policy of district government that published the decree No. 44/02.188.45/HK/II/2005) which is supported by society and recommendation from few instances are effort to support Wehea Forest Protected management. The substances of the policies that published by district government and other instances more leads to manage this area in conservation function that protected function. That policy did not reach the result as expected yet because the decree about the determination of this area to be a protected forest from Department of Forestry was not published yet. Keyword : Wehea Forest Protections, Regional Policy, GAP Analysis.